Trend and spatial-temporal variation of drought characteristics over equatorial East Africa during the last 120 years - Omondi, Onyango Augustine; Lin, Zhaohui (Frontiers in Earth Science, 2023)
Centennial drought characteristics in Equatorial East Africa (EEA) is investigated using the Standardized Precipitation Evapotranspiration Index (SPEI) derived from the Climatic Research Unit (CRU) dataset. The spatial pattern of drought distribution, as well as drought duration, intensity and frequency, are analyzed for SPEI at a 3-month timescale for March-April-May (MAM) season. Rotated Empirical Orthogonal Function (REOF), Mann-Kendall method (MK), and wavelet analyses are used to study drought's spatial pattern, trend, and periodicity. The result of the principal component analysis returned six homogenous drought sub-regions. A low drought frequency characterizes EEA (< 20%). The drought in the MAM season lasts between 2.2 to 2.8 months. Overall, the result showed a weak long-term drying trend for most parts of EEA that were significant in some sub-regions and insignificant in others. An increase in drought areal extent after the 1980s could be ascribed to the increase in potential evapotranspiration (PET) and is consistent with the negative trend in SPEI value over the 6 sub-regions. The apparent increase is mainly attributed to the increase in moderate and severe droughts area rather than extreme drought areas. The spectral analysis further reveals that inter-annual drought variability with periodicities less than eight years dominates in all sub-regions of East Africa, which is associated with the critical role of El Nino in driving the drought variations in East Africa.